Non-bleeding spontaneous rupture of hepatocellular carcinoma - Mahibul Islam (Nigerian Journal of Surgery, 2013)
Rupture of hepatocellular carcinoma (HCC) is not uncommon and most ruptured HCC present with hemoperitoneum and hemorrhagic shock. Management of ruptured HCC is different than non-ruptured one. Short- and long-term mortality increases following rupture of HCC with increasing chances of tumor dissemination. We describe a case with non-bleeding spontaneous rupture of HCC. A 62-year-old male patient was admitted to our institute hospital with mild to moderate pain in the right upper part of the abdomen. He lost appetite and weight. Ultrasonography of the abdomen was performed and it suggested HCC and ascites. Triple phase computer tomography revealed HCC in segments 6 and 7 of liver with typical radiological characteristics. Portal vein was thrombosed. No extravasation of dye was seen. Ruptured of tumor through liver capsule was seen with necrosis and hemorrhage in the center of the tumor. Non-bleeding ruptured HCC has not been reported in the literature to the best of our knowledge. We herein describe this rare case.